Information security and mutual trust as determining factors for information technology outsourcing success - Shittu, Abdul Jaleel Kehinde; Ahlan, Abdul Rahman; Sheik Osman, Wan Rozaini (Academic Journals, 2012)
Information security and mutual trust have been the major stumbling blocks in the adoption of information technology outsourcing (ITO), clients were skeptical about possibilities of ITO as a mean of bridging the gap between information technology (IT) and business community. This development had made it difficult for ITO to be practiced in isolation. Business transaction is done between two or more interested parties, it is imperative for the parties to operate successfully only in an environment where mutual trust and information security are guaranteed and respected. This research looks into the impact of information security and mutual trust on ITO contracts, by investigating how the ITO suppliers (big organizations and small and medium enterprises SME) in Malaysia interpret the concept of information security and mutual trust and their effects on ITO dealings. This research finds out that information security and mutual trust were considered as the bedrocks of ITO success especially among the SMEs while big organizations see information security and mutual trust as organization’s ladder to success. Though, many interviewees considered information security as an integral part of mutual trust. Interviews were conducted among some ITO suppliers in Malaysia and MAXQDA is used as the analysis tool.